DNA metabarcoding on repeat: Sequencing data of marine macrobenthos are reproducible and robust across labs and protocols. (June 2023) - Van den Bulcke, Laure; De Backer, Annelies; Wittoeck, Jan; Beentjes, Kevin; Maes, Sara; Christodoulou, Magdalini; Martinez Arbizu, Pedro; Sapkota, Rumakanta; Van der Hoorn, Berry; Winding, Anne; Hostens, Kris; Derycke, Sofie
Highlights: A standardized protocol yields reproducible bulkDNA metabarcoding results. Highly abundant and large species are shared most often between laboratories. Need for standardization when comparing alpha diversity between different studies. Betadiversity patterns are robust to changes in the metabarcoding wetlab protocol. Abstract: DNA metabarcoding can be used in marine environmental monitoring if results are reproducible between labs and robust against modifications to the lab protocol. In this interlaboratory study, we conducted a ring test where subsamples of blended macrobenthos samples were distributed to four laboratories located in Belgium, the Netherlands, Germany and Denmark. Samples were processed by a standardized lab protocol and by an adapted protocol, and the resulting datasets were analyzed with the same bioinformatics pipeline. Different biodiversity indicators were calculated. Our results show that bulkDNA metabarcoding of marine macrobenthos offers a highly reproducible assessment of alpha diversity patterns when using a standardized protocol, since comparable species numbers, Shannon indices and Inverse Simpson indices were found between laboratories. Especially high abundant species and species with large body sizes were shared between the laboratories. The need for using a standardized protocol to enhance comparability in alpha diversity between different studies was shown. Beta diversity patterns are less subjected to changes in the metabarcoding protocol and were almost identical between different laboratories, as the main clustering was always based on the macrobenthic community, independent of the used protocol or the laboratory that conducted the work. We conclude that DNA metabarcoding for marine environmental monitoring is an appropriate method when the aim is to study changes in community patterns and advocate its implementation in routine monitoring programs of national and European authorities, providing that a standardized protocol is implemented and/or a detailed description of the protocol is available.